Introduction to Genomics - Lesk, Arthur M. (New York Oxford University Press, 2012)
Our genome is the blueprint to our existence: it encodes all the information we need to develop from a single cell into a hugely complicated functional organism. But it is more than a static information store: our genome is a dynamic, tightly-regulated collection of genes, which switch on and off in many combinations to give the variety of cells from which our bodies are formed. But how do we identify the genes that make up our genome? How do we determine their function? And how dodifferent genes form the regulatory networks that direct the processes of life?Introduction to Genomics is a fasci.
Include Color Illustration and Index
Keywords: Genomics